Understanding African music – Listen and learn: music made easy – For future generations: Hugh Tracey and the International Library of African Music – Sound of Africa – Music of Africa – Historical recordings by Hugh Tracey – ILAM and Ubuntu Publishing – The Dhow Countries Music Academy: Zanzibar (International Library of African Music, 2017)
pages: 182-189
Keywords: African Music